2023
DOI: 10.3390/cells12212581
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Based Models of ‘Cytokine Release Syndrome’ Endorse CD40L and Granulocyte–Macrophage Colony-Stimulating Factor Knockout in Chimeric Antigen Receptor T Cells as Mitigation Strategy

Ala Dibas,
Manuel Rhiel,
Vidisha Bhavesh Patel
et al.

Abstract: While chimeric antigen receptor (CAR) T cell therapy has shown promising outcomes among patients with hematologic malignancies, it has also been associated with undesirable side-effects such as cytokine release syndrome (CRS). CRS is triggered by CAR T-cell-based activation of monocytes, which are stimulated via the CD40L–CD40R axis or via uptake of GM-CSF to secrete proinflammatory cytokines. Mouse models have been used to model CRS, but working with them is labor-intensive and they are not amenable to screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
(58 reference statements)
1
2
0
Order By: Relevance
“…Simulating a reduction of the different activation mechanism showed that targeting CD40 leads to the most substantial reduction in IL-6 peak height, causing an average reduction of 42% in the case of constant blocking and 30% reduction when blocking from day 2 after infusion to 1 day after CAR-T cell peak. This aligns with a recent cell-based in vitro model for CRS that showed that IL-6 supernatant levels decreased 20-30% when blocking cytokine release by bystander macrophages with neutralizing antibodies for GM-CSF and CD40, and decreased 30-40% due to the genetic disruption of the CD40L and/or CSF2 knock-out CAR-T cells [32].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Simulating a reduction of the different activation mechanism showed that targeting CD40 leads to the most substantial reduction in IL-6 peak height, causing an average reduction of 42% in the case of constant blocking and 30% reduction when blocking from day 2 after infusion to 1 day after CAR-T cell peak. This aligns with a recent cell-based in vitro model for CRS that showed that IL-6 supernatant levels decreased 20-30% when blocking cytokine release by bystander macrophages with neutralizing antibodies for GM-CSF and CD40, and decreased 30-40% due to the genetic disruption of the CD40L and/or CSF2 knock-out CAR-T cells [32].…”
Section: Discussionsupporting
confidence: 89%
“…Currently, the primary drug used to address CRS is Tocilizumab, a monoclonal antibody that acts as an IL-6 antagonist [12]. However, targeting macrophage activation with GS-CSF and CD40 antibodies has also been explored in cell-based studies [32].…”
Section: Targeted Interventions To Control Macrophage Activationmentioning
confidence: 99%
“…The granulocyte-macrophage colony-stimulating factor (GM-CSF) plays a vital role in the clinical manifestations of CRS and ICANS [111]. The knockout of genes interplaying in the transcription of GM-CSF reduced the inflammation mediated by cytokine release in patients who received CAR-T immunotherapies [112][113][114][115][116]. Guercio et al conducted a study in vivo and administered the inducible caspase 9 (iC9) gene in a model of CAR-T cell lines.…”
Section: Crs and Icans As Endotheliopathies: The Genetic Backgroundmentioning
confidence: 99%